The effect of shear stress on the formation and removal of Bacillus cereus biofilms - Madalena Lemos (2015)
The influence of the shear stress (tau(w)) under which biofilms were formed was assessed on their susceptibility to removal when exposed to chemical and mechanical stresses. A rotating cylinder reactor was used to form biofilms, allowing the simulation of tau(w) conditions similar to those found in industrial settings, particularly in areas with low tau(w) like elbows, corners, valves and dead zones. Bacillus cereus was used as a model bacterium for biofilm formation. Biofilms were formed on AISI316 stainless steel cylinders under different tau(w) (estimated at 0.02, 0.12 and 0.17 Pa) for 7 days. Some phenotypic characteristics, including thickness, biomass production, cellular density and extracellular proteins and polysaccharides content were assessed. Biofilm density was found to increase significantly with tau(w) while the thickness decreased. Also, biofilms formed at 0.02 Pa had lowest biomass content, cell density and extracellular polysaccharide content. Those characteristics were not statistically different for the biofilms formed under 0.12 and 0.17 Pa. Ex situ tests were performed by treating the biofilms with the biocide benzyldimethyldodecyl ammonium chloride (BDMDAC), followed by exposure to increasing tau(w) conditions, up to 1.84 Pa (whereas the maximum tau(w) used during growth was 0.17 Pa). The biofilms formed under low tau(w) were more resistant to removal caused by the BDMDAC action alone. Those formed under higher rw were more resistant to the mechanical and the combined chemical and mechanical treatments. The amount of biofilm remaining on the cylinders, after both treatments was statistically similar for biofilms formed under 0.12 and 0.17 Pa. The resistance of biofilms to removal by mechanical treatment (alone and combined with BDMDAC) was related to the amount of matrix polysaccharides. However, none of the methods investigated were able to remove all the biofilm from the cylinders.